Malana : globalization of a Himalayan village - Veverka, Jeremy; Veverka, Jesse (2010)
In the misty foothills of India's Himalayan mountain range sits an isolated village called Malana. The construction of a road up the once remote Malana valley brings with it promises of new opportunities and development. Will the Malanese be able to preserve their unique culure, or will it be swept away by the forces of globalization.